Tibiofemoral Contact Biomechanics Following Meniscocapsular Separation and Repair - Dugas, J. R.; Barrett, A. M.; Beason, D. P.; Plymale, M. F.; Fleisig, G. S. (International Journal of Sports Medicine, 2015)
Meniscocapsular separations are often seen in knees with other intra-articular pathology. The consequences of these tears with regard to knee contact mechanics are currently unknown, and the biomechanical advantages of repair have not been measured. We hypothesize that tears to the meniscocapsular junction will cause an increase in tibiofemoral contact pressure and a decrease in contact area, with a return to more normal conditions after repair. 10 fresh-frozen cadaver knees each underwent 10 cycles of axial compressive loading in full extension under three different testing conditions: intact, meniscocapsular separation, and repair. A pressure sensor matrix was inserted into the medial joint space and used to measure magnitude and location of contact pressure and area. Mean contact pressure increased from 0.80±0.17 MPa in the intact knee to 0.88±0.19 MPa with separation, with a decrease to 0.78±0.14 MPa following repair. Peak pressures followed a similar trend with 2.59±0.41, 3.03±0.48, and 2.84±0.40 MPa for the same three groups, respectively. While none of the changes seen was statistically significant, even these small changes would potentially create degenerative changes at the articular surface over prolonged (i. e., months or years) standing, walking, and activity in the unrepaired state.
Keywords: meniscus; knee; mechanics